2018
DOI: 10.2147/cmar.s177043
|View full text |Cite
|
Sign up to set email alerts
|

Elevated <em>DKK1</em> expression is an independent unfavorable prognostic indicator of survival in head and neck squamous cell carcinoma

Abstract: PurposeDKK1 is an antagonist of the Wnt signaling pathway that has various roles in human physiology. Notably, aberrant DKK1 expression is observed in several cancers. In this retrospective study, we assessed the association between DKK1 expression levels and head and neck squamous cell carcinoma (HNSCC) and its prognostic value.Materials and methodsUsing RNA-seq data from HNSCC tumors (N=520) and adjacent normal tissue (N=44) in The Cancer Genome Atlas, we evaluated DKK1 expression levels. Additionally, we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Among these 27 genes enrolled in IRGS, six genes (ULBP1, CCR6, CCL22, ROBO1, DKK1 and PDGFA) have previously shown to correlate with the tumorigenesis of HNSCC [20][21][22][23][24][25]. As reported, CCR6 Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Among these 27 genes enrolled in IRGS, six genes (ULBP1, CCR6, CCL22, ROBO1, DKK1 and PDGFA) have previously shown to correlate with the tumorigenesis of HNSCC [20][21][22][23][24][25]. As reported, CCR6 Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Reliable prognostic biomarkers are needed to identify patients with the highest risk of unfavorable survival outcomes. Numerous studies have highlighted the biomarkers associated with the pathogenesis and biology of HNSCC [14,[20][21][22][23][24][25]. Unfortunately, the accuracy of their survival evaluations remains limited and they have not yet been applied in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes hold a decisive place in expression of cytokine and its receptors. Overexpression of DKK1, an identified proinflammatory cytokine in quite a number of cancers (Chae and Bothwell, 2019), could boost malignant cell proliferation, migration, and invasiveness and give rise to unfavorable clinical outcomes in HNSCC (Shi et al, 2014;Gao et al, 2018). HBEGF serves as a crucial component of EGFR, mediating tumor cell proliferation and bringing about cetuximab resistance (Hatakeyama et al, 2010;Huang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, univariate CPH analysis was performed to analyze the relations between the expression of genes and the OS of patients with LUAD, and the results exhibited that 99 genes were associated with the OS of LUAD patients. LASSO (34) was introduced in order to improve the prediction accuracy and interpretability of regression models by forcing certain coefficients to be set to zero, and effectively to choose a simpler model that did not include those coefficients. Based on this, the above 99 genes were included into a LASSO penalized CPH model, and as a result 4 genes with none-zero coefficients in this model were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This gene played a role in embryonic development and might be important in bone formation in adults [32]. Elevated expression of this gene had been observed in numerous human cancers and it corresponding protein promoted proliferation, invasion and growth in several kinds of cancer cell lines [33,34]. Aufderklamm S et al demonstrated that DKK-1 could inhibit osteoblast activity by blocking the Wnt pathway, which led to progression of metastatic prostate cancer [35].…”
Section: Discussionmentioning
confidence: 99%